Hybrid Solar: A Review on Photovoltaic and Thermal Power Integration. (6th December 2012) - Chow, T. T.; Tiwari, G. N.; Menezo, C.
Abstract : The market of solar thermal and photovoltaic electricity generation is growing rapidly. New ideas on hybrid solar technology evolve for a wide range of applications, such as in buildings, processing plants, and agriculture. In the building sector in particular, the limited building space for the accommodation of solar devices has driven a demand on the use of hybrid solar technology for the multigeneration of active power and/or passive solar devices. The importance is escalating with the worldwide trend on the development of low-carbon/zero-energy buildings. Hybrid photovoltaic/thermal (PVT) collector systems had been studied theoretically, numerically, and experimentally in depth in the past decades. Together with alternative means, a range of innovative products and systems has been put forward. The final success of the integrative technologies relies on the coexistence of robust product design/construction and reliable system operation/maintenance in the long run to satisfy the user needs. This paper gives a broad review on the published academic works, with an emphasis placed on the research and development activities in the last decade.